Role of oqxA and oqxB Genes in the Development of Multidrug Resistant Phenotype among Clinical Klebsiella pneumoniae Isolates from Various Cases - Mustafa, Mustafa Suhel; Abdullah, Rana Mujahid (Iraqi Journal of Science, 2020)
This study investigated the prevalence of oqxA and oqxB genes and their effective roles in the development of multidrug resistant (MDR) phenotype among clinical isolates of Klebsiella pneumoniae. Out of 150 clinical samples, 50 (33%) isolates were recognized as K. pneumoniae according to the morphological and biochemical properties. The minimum inhibitory concentrations (MICs) assay revealed that the resistance values of the isolates were 43 (86%) against ceftriaxone (4- ≥64 µg/ml), 42 (84%) against ceftazidime (16- ≥64 µg/ml), 41 (82%) against cefepime (≥16 µg/ml), 21 (42%) against ertapenem (≥8 µg/ml), 18 (36%) against imipenem (4- ≥16 µg/ml), 15 (30%) against ciprofloxacin (≥4 µg/ml), 11 (22%) against levofloxacin (≥8 µg/ml), 45 (90%) against nitrofurantoin (128- ≥512 µg/ml), 36 (72%) against trimethoprime-sulfamethoxazole (≥320 µg/ml), and 4 (8%) against tigecycline (≥8 µg/ml). Genotype detection revealed that oqxA was found in 48 (96%) of K. pneumoniae isolates, whereas oqxB was found in 6 (12%) isolates. The MDR phenotype was observed in 40 (80%) isolates, of which 38 (95%) were harbored oqxA and/or oqxB genes. DNA sequencing of oqxA revealed the presence of three silent mutations. The phylogenetic tree of oqxA variants showed a significant deviation of these variants from K. pneumoniae species. The high prevalence of oqxA among K. pneumoniae isolates may contribute to the reduction of their susceptibility to multiple antimicrobial agents.